Effects of high-intensity interval training on physical fitness in trained adolescent athletes: a systematic review and meta-analysis - Zhang, F.; Liu, Y.; Liu, J.; Li, C.; Liu, Z.; Yeremenko, O. (Frontiers in Physiology, 2026)
Background: This systematic review and meta-analysis evaluated the effects of HIIT-based interventions on cardiorespiratory fitness, jump, sprint, change-of-direction, and repeated sprint ability in trained adolescent athletes, and explored potential moderators of these effects.